Multiplex Mutagenically Separated PCR: Diagnosis of β-Thalassemia and Hemoglobin Variants - J.-G. Chang; H.-J. Liu; J.-M. Huang; T.-Y. Yang; C.-P. Chang (BioTechniques)
A rapid and simple method, termed multiplex mutagenically separated PCR (MSPCR), was developed to detect several molecular defects in the hemoglobin gene in one PCR. This technique, in which differentsize allele-specific primers were used, specifically amplified both normal and mutant alleles of the globin gene in the same reaction. Subsequent gel electrophoresis showed at least one of the two allelic products at the same locus or two of the several allelic products of different loci and provided a within-assay quality control for the exclusion of false-negative results. In our study, the four most common β-thalassemia mutations, together with four other common hemoglobin variants in Chinese, were tested. Using multiplex MS-PCR 6 to 12 primers were added simultaneously into one reaction tube to identify one to four mutations. Not only is this multiplex MS-PCR method reliable and non-isotopic, the results can be obtained in less than one working day.